2022
DOI: 10.18006/2022.10(3).544.553
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy toward the COVID-19 vaccine among the Malaysian population

Abstract: COVID-19 is a potentially fatal infectious disease that requires effective vaccines to keep the outbreak under control. Despite the ongoing efforts for an effective vaccine, public hesitancy towards vaccines is now one of the main concerns to the global health in containing this global pandemic. Thus, this preliminary study was carried out to assess the degree of COVID-19 vaccine hesitancy among the general public in Malaysia and to identify the underlying reasons for their hesitancy by using 5C psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…Studies from Switzerland and Bangladesh yielded similar results in the aspect of constraint ( 72 , 75 ). As opposed to our finding, previous research has found that constraint was a significant predictor of vaccine attitudes ( 73 ). All in all, the 5C model of psychological antecedents were important predictors of vaccine attitude in our study population.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Studies from Switzerland and Bangladesh yielded similar results in the aspect of constraint ( 72 , 75 ). As opposed to our finding, previous research has found that constraint was a significant predictor of vaccine attitudes ( 73 ). All in all, the 5C model of psychological antecedents were important predictors of vaccine attitude in our study population.…”
Section: Discussioncontrasting
confidence: 99%
“…Parents with higher collective responsibility were found to have lower vaccine hesitancy as people would be willing to receive vaccination for the benefits of others. Collective responsibility was found to be a strong predictor of vaccine acceptance in many studies across the globe (72)(73)(74)76). In our study, the only psychological antecedent in the 5C model that was not associated with negative vaccination attitudes was constraint.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations